ANALISIS NILAI-NILAI GOTONG ROYONG SISWA DALAM PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) KELAS IV DI SEKOLAH DASAR - Andika Samudra; Maryono; Muhammad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the gotong royong values among fourth-grade A students at SD Negeri 057/I KM V Muara Tembesi, focusing on the Pancasila Student Profile Reinforcement Project (P5) through a quantitative descriptive method using structured observations. The research instrument was designed around seven indicators categorized into three main aspects: the collaboration aspect, which includes cooperation (X1), communication (X2), positive interdependence (X3), and social coordination (X4); the caring aspect, comprising social environmental responsiveness (X5) and social perception (X6); and the sharing aspect, represented by the sharing indicator (X7). Results indicate that a majority of students fall into the Good and Very Good categories for collaboration and caring aspects, with the highest scores in positive interdependence (X3) at 92% and social environmental responsiveness (X5) at 77%. Additionally, 77% of students also achieved Good and Very Good ratings in the sharing aspect (X7). These results suggest that the P5 implementation has effectively fostered the internalization of gotong royong values among students within the framework of project-based learning at the elementary level.